Pengaruh Transformasi Kurikulum Terhadap Kompetensi Mahasiswa Melalui Keterlibatan Belajar: Analisis Sem-PLS Pada Program Studi PAI - Ceshelya Astra; Aniska Septi Sabena; Deri Wanto; Muhammad Idris; Epa Kristina (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
The study aims to analyze the impact of curriculum transformation on student competence thru learning engagement as a mediating variable in the Islamic Religious Education Study Program (PAI). The approach used is quantitative with an explanatory design. Data were collected thru a Likert scale-based questionnaire distributed to students who had participated in learning with the transformed curriculum. Data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) to test the relationships between variables and mediation effects. The research results show that curriculum transformation has a positive effect on student learning engagement and competence. Learning engagement has also been proven to have a positive impact on student competence. Additionally, learning engagement acts as a mediating variable that strengthens the influence of curriculum transformation on student competence. These findings indicate that the effectiveness of curriculum transformation is not only determined by changes in the curriculum structure but also by the level of student engagement in the learning process. Thus, the improvement of student competencies can be optimally achieved thru an adaptive curriculum and learning that encourages active student engagement.